Is conformism desirable? Network effects, location choice, and social welfare in a duopoly - Luca Savorelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
In this paper we study a duopoly where the network eect is nonmonotone and the network can be overloaded. The firms choose prices and locations endogenously, and the agent's utility is influenced by the number of people patronizing the same firm she does. We determine the market equilibrium, and we study how the network effect influences social welfare. We compare this setting with the standard horizontal differentiation model with no network effects to understand whether and how conformism is socially desirable. The results show that whether network effects are desirable depends on how people are conformist, and whether overloading is feasible. If overloading is not possible (in either of the firm's network), and the total consumers' mass is sufficiently high, a network effect which is slightly concave increases social welfare. By contrast, if overloading is feasible, and the total consumers' mass is sufficiently small, social welfare is increased if the network effect is more concave than in the previous case.
Keywords: L14; D62; 330